Teaching Reading Using Storyberries for Indonesian Young Learners - Herda, Rozanah; Nuraeningsih, Nuraeningsih; Kusumastuti, Dyah; Principe, Regine (Universitas Nahdatul Ulama Surabaya, 2023)
Teaching reading for young learners in this 21st-century learning demands teachers to be creative and consider the educational effect on students through technology-enhanced language learning. Therefore, the characteristics of students categorized as young learners should be considered, so the process of designing teaching scenarios, including the material and media, can be administered right on the target. At this point, teaching reading as one of the parts of literacies in the EFL context challenged teachers to simultaneously build students' reading motivation and ability in this digital era. This mixed-method study involved 31 young learners in one primary school in Yogyakarta, Indonesia. This study had two research questions: 1) How is the student's reading activity during the implementation of Storyberries? And 2) How is the student's reading achievement after being taught using Storyberries? Storyberries, a treatment used in this study, was a free online audiobook that provides many short stories that can be adjusted to readers' age, the duration of reading need, and reading interest. The design used in this study was an Exploratory Sequential Design, where the qualitative method preceded the quantitative one. The instruments used in this study were classroom observation sheets and tests. The three concurrent flows as a triangulation technique were used to analyze the qualitative data, while normality and descriptive statistics using SPSS version 25 were administered to analyze the quantitative data. The study's findings revealed that teachers used good pedagogical aspects to integrate Storyberries into the reading classroom and successfully enhanced students' reading motivation and proficiency. This pedagogical impact is expected to be implemented to the broader scope of teaching reading for young learners' needs. Keywords: Teaching reading; storyberries; young learners